Interrelation of the maintenance endotehelin 1-21 in serum of blood and indicators of daily monitoring of arterial pressure with diabetic nephropathy in children and the teenagers of diabetes mellitus type 1 - A. V. Enert; S. N. Ivanov; Yu. G. Samoilova (Бюллетень сибирской медицины)
Daily monitoring arterial pressure (DMAP) and definition endotehelin 1-21 immunofermentat a method was perfermed in 79 children and teenagers with type 1 diabetes mellitus (DM1) in the age 10—18 years, with duration of disease 2—16 years auskultative a method on the apparate “Shiller BR-102 plus” (Switzerland). Depending on a degree of expressiveness diabetic nephropathy (DN) patients have been distributed on three groups: 1st — normalalbuminuria (n = 31), 2nd — microalbumiuria (n = 32), 3rd — proteinuria (n = 16) and 16 person the control group comparable on a floor and age. At children and teenagers with DM1 according to DMAP, attributes of a labile arterial hypertension (AH), met at 34,1%, stable at 25,5%. Frequency of revealing of stable forms АГ depend on expressiveness DN. The daily rhythm the AP at patients DM1 was characterized by a low degree of night decrease the AP. 47,1% patients 1st groups, 72,7% patients 2nd and 75% patients 3rd had no adequate decrease the AP at night. Communication between the raised level endotehelin 1-21 with development and progressing diabetic nephropathy, and also with indicators diastolic AP is revealed.